The effect of colour on students' learning experience and creativity in design schools - Dash, Shanta Pragyan; Vittal, Varshini (Creativity Studies, 2025)
Research indicates that colours used in learning environments can influence student performance in terms of creativity. However, the impact of different shades of classroom walls affect students’ learning experience regarding creativity and willingness in a design school has not been explored in past research. This study aims to analyse the effects of various colours on students’ creativity in a design school based on hue, chroma, and value attributes. The colour of the walls has a unique effect on how successfully college students perform in the classroom. This study built six virtual classrooms with red, blue, and green walls, each with two distinct values and chroma, to determine a good wall colour to encourage creativity. College students’ perceptions were also gathered at the same time. According to the subjective survey, the colours green-yellow (105, 131, 130) and blue-green (48, 132, 154) on the walls had a mildly positive effect on the students. In contrast, green-yellow (114, 127, 82) and blue-green (37, 150, 190) positively impacted the student’s ability to focus and desire to work. Red (196, 88, 88) and red (231, 49, 69) had a negative effect on the students. These findings highlight the potential of carefully chosen colours to enhance the learning environment and improve student outcomes in design schools.